Entanglement of Spatial and Energy Segmentation for C1 Pathways in CO2 Reduction on Carbon Skeleton Supported Atomic Catalysts (Adv. Energy Mater. 14/2022). Issue 14 (14th April 2022) - Sun, Mingzi; Wong, Hon Ho; Wu, Tong; Dougherty, Alan William; Huang, Bolong
Abstract : Single Atomic Catalysts In article number 2103781 Bolong Huang and co‐workers propose a comprehensive mapping of the complete C1 pathways of CO2 reduction on graphdiyne‐based single atomic catalysts (SACs) across the full range of transition metals and lanthanides. The influence of thermodynamic and spatial factors on electrochemical performance are assessed. This work supplies an in‐depth understanding of the impact of electroactivity modulations and reaction processes on SAC performance.